Identification of Sp1-elements in the promoter region of human homeobox gene NKX3.1 - Yu, Chun-xiao; Jin, Tong; Chen, Wei-wen; Zhang, Peng-ju; Liu, Wen-wen; Guan, Heng-yun; Zhang, Ju; Liu, Qing-wei; Jiang, An-li (Molecular biology reports, 2009)
NKX3.1 is a prostate-specific homeobox gene related strongly to prostate development and prostate cancer. However, little is known about the mechanism for regulation of NKX3.1 in prostate cancer. With RT-PCR and western blot, we found that NKX3.1 expression was enhanced by over-expression of Sp1 at both the mRNA and protein levels in prostate cancer LNCaP cells. To identify the Sp1-elements in the promoter region of NKX3.1 , a 521 bp-promoter of human NKX3.1 gene containing three possible Sp1-elements was cloned into the upstream of the luciferase reporter gene in pGL 3 -basic plasmid. With deletion mutation analysis, plasmid construction, EMSA and oligonucleotide decoy technique, two Sp1-elements which located between +29 to +43 and −60 to −46 of NKX3.1 gene were identified and proven to be functional elements. It will be important to further study on the functions and the regulatory mechanisms of Sp1 element in NKX3.1 gene expression.